An investigation of the certain class of multivalent harmonic mappings - Özkan Uçar, Hatice Esra; Aydoğan, Seher Melike; POLATOĞLU, YAŞAR (My University, 2016)
The main purpose of the present paper is to investigate some properties of the certain class of sense-preserving p-valent harmonic mappings in the open unit disc D = {z is an element of C parallel to z vertical bar < 1}.